PENERAPAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA TIDORE KEPULAUAN - Rachman, Saiful (Jurnal Akrab Juara, 2018)
The implementation of Shrimp Law Number 22 Year 2009 on Traffic and Road Transport tidore islands city is not something that is easily implemented by law enforcement authorities in this case the Tidore Island police force islands. This is due to several things. In addition to the factors because this law is not comprehensive socialization to the general public, so that public understanding of Law Number 22 Year 2009 is still very / minimal, also due to cultural factors of society and facilities and infrastructure of inadequate traffic form of signs roads and other infrastructure. All this causes the impediment of the implementation of Law no 22 of 2009 on Road Traffic and Transportation in Tidore Islands City in particular. keywords : traffic law, application, community